2002
DOI: 10.1002/pros.10098
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and prostate cancer cell proliferation: Interplay with castration, epidermal growth factor, and androgen sensitivity

Abstract: Together with previous data, the present results indicate synergistic action of melatonin and castration in inhibiting the growth of androgen-sensitive LNCaP tumor. Androgen-sensitive prostate cancer cell proliferation may be modulated by opposite changes in cyclin D1 levels induced by activated MT(1) and EGF receptors. In androgen-insensitive prostate cancer cells, MT(1) receptor-mediated signal transduction may become defective not only through changes in membrane receptor protein expression and/or functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 32 publications
5
64
2
Order By: Relevance
“…2B), a 4-fold increase in cell proliferation was observed. These findings parallel the same proliferative response found by Iwamura et al (14) and Siu et al (15) and demonstrate the expected functional activity of DHT, IGF-I, and EGF in the LNCaP PCa cell model. Because it has been shown that PSA mRNA is stimulated on DHT treatment (16), the action of DHT in our system was further demonstrated by measuring the up-regulation of PSA mRNA in LNCaP cells by quantitative PCR.…”
Section: Resultssupporting
confidence: 90%
“…2B), a 4-fold increase in cell proliferation was observed. These findings parallel the same proliferative response found by Iwamura et al (14) and Siu et al (15) and demonstrate the expected functional activity of DHT, IGF-I, and EGF in the LNCaP PCa cell model. Because it has been shown that PSA mRNA is stimulated on DHT treatment (16), the action of DHT in our system was further demonstrated by measuring the up-regulation of PSA mRNA in LNCaP cells by quantitative PCR.…”
Section: Resultssupporting
confidence: 90%
“…30). Several in vitro studies have reported a reduction in the growth of malignant cells and/or tumors of the breast (31)(32)(33)(34)(35) prostate (36)(37)(38)(39)(40)(41), and other tumor sites (42)(43)(44)(45)(46) by both pharmacologic and physiologic doses of melatonin. In rodent models, pinealectomy has been found to enhance tumor growth (47), and exogenous melatonin administration has shown anti-initiating (48) and oncostatic (49)(50)(51)(52) activities in various chemically induced cancers as well as in virus-transmitted tumors in mice (53).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…After the first observation that in MCF-7 cells in vitro, 1 nM melatonin reduces tumor cells invasiveness in Falcon invasion chambers (Cos et al, 1998), the oncostatic properties of melatonin have been thoroughly investigated. Melatonin acts synergistically with castration in inhibiting growth of androgen-sensitive LNCaP tumor through opposite changes in cyclin D1 levels induced by activated MT1 and EGF receptors (Siu et al, 2002). As MT1 receptors are clearly involved in androgen-sensitive LNCaP, but not in androgeninsensitive PC-3 cells (Xi et al, 2001), it is likely that the antiproliferative action of melatonin in LNCaP tumor growth is associated with MT1 receptor protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various experimental prostate cancer models, hormone (androgen)-sensitive and hormone (androgen)-insensitive metastatic human prostate cancer cell lines are widely used for the experimental evaluation of pharmacological agents with therapeutic potential for the disease (Cho et al, 2011). In particular, the growth of the androgen-independent but androgen-sensitive (responsive) human LNCaP prostate cancer cells has been demonstrated to be inhibited by the pineal gland indoleamine hormone both in vitro and in vivo in a nude mice xenograft model (Siu et al, 2002;Xi et al, 2000). The antiproliferative action of melatonin seems to be mediated in part by means of MT1 receptor activation and partly by means of attenuation of dihydrotestosterone-induced calcium influx model (Xi et al, 2000).…”
Section: Lncap Prostate Cancer Growth In Vivomentioning
confidence: 99%